Recent Advances in Short QT Syndrome - Campuzano, Oscar; Sarquella-Brugada, Georgia; Cesar, Sergi; Arbelo, Elena; Brugada, Josep; Brugada, Ramon (Frontiers in Cardiovascular Medicine, 2018)
Short QT syndrome is a highly malignant inherited cardiac disease characterized by ventricular tachyarrhythmias leading to syncope and sudden cardiac death. It is responsible of lethal episodes in young people, mainly infants. International guidelines establish diagnostic criteria with the presence of a QTc ≤340 ms in the electrocardiogram despite clinical diagnostic values remain controversial. In last years, clinical diagnosis, risk stratification as well as preventive therapies have been improved due to identification of pathophysiological mechanisms. The only effective option is implantation of a defibrillator despite Quinidine may be at times an effective option. Currently, a limited number of rare variants have been identified in seven genes, which account for nearly 20%-30% of families. However, some of these variants are associated with phenotypes showing a shorter QT interval but no conclusive diagnosis of Short QT syndrome. Therefore, an exhaustive interpretation of each variant and a close genotype-phenotype correlation is necessary before clinical translation. Here, we review the main clinical and genetic hallmarks of this rare entity.